Passive Fault-Tolerant Control Strategies for Power Converter in a Hybrid Microgrid - Saeedreza Jadidi; Hamed Badihi; Youmin Zhang (Energies, 2020)
Control of AC/DC pulse-width modulation (PWM) power electronic converter, referred to as “AC/DC PWM converter”, is vital to the efficient regulation of power flow between AC and DC parts of a hybrid microgrid. Given the importance of such converters in AC/DC microgrids, this paper investigates the design of fault-tolerant control for AC/DC PWM converters in the presence of microgrid faults. In particular, two novel fault-tolerant schemes based on fuzzy logic and model predictive control are proposed and implemented in an advanced hybrid microgrid benchmark in MATLAB/Simulink environment. The considered hybrid microgrid consists of dynamic loads and distributed energy resources including solar photovoltaic arrays, wind turbines, and battery energy storage systems. The proposed schemes especially target the fault effects due to common power-loss malfunctions in solar photovoltaic arrays in the presence of microgrid uncertainties and disturbances. The effectiveness of proposed fault-tolerant control schemes is demonstrated and compared under realistic fault scenarios in the hybrid microgrid benchmark.